Verification of fossil CO2 emissions from Swiss cement factories using direct and indirect 14CO2 measurements - Dylan Geissbühler; Thomas Laemmel; Mathieu Antoni; Philip Gautschi; Lukas Wacker; Sönke Szidat (Atmospheric Environment: X, 2025)
Cement production currently emits approximately 8 % of global CO2. However, the fossil content of these emissions can vary significantly due to methods used to reduce fossil emissions, such as the increased use of alternative fuels. Here, we investigated three CO2 sampling methods used to analyse 14CO2 and estimate the fossil fraction (in terms of F14C) of emissions from three Swiss cement factories. First, direct stack exhaust gas sampling was conducted at a main study site over 6 months and 14CO2 measurements were compared with 14C values from producer fuel use data. A positive offset in F14C was observed with theoretical values compared to the measurements. This could be reduced by adjusting the assumed 14C content of some fuels, particularly shredded wood waste. Second, repeated downwind CO2 emission plume sampling campaigns were carried out at all sites, allowing for a remote estimation and comparison of their F14C signatures. These measurements yielded realistic average values but also demonstrated sensitivity to local wind conditions, i.e. wind speed and direction. Lastly, we analysed the bulk 14C content of tree leaves collected around each site to assess their long-term atmospheric fossil CO2 exposure. Although the observed 14C depletion and fossil fraction were generally small (close to uncertainty ranges), trees near the factories consistently showed lower F14C values than background trees. Direct stack exhaust gas sampling proved to be the most reliable approach for quantifying fossil CO2 emissions from cement production. Crucially, adjustments made to fuel 14C contents to match measurements suggested an underestimation of fossil CO2 emissions from the producer at our main site by more than 2 %.